1996
DOI: 10.1111/j.1399-0039.1996.tb02571.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of loss of HLA class I expression on colorectal tumor cells

Abstract: For several years this laboratory has studied the expression of HLA class I on established colorectal tumor cell lines and on fresh tumors. We review here the mechanisms by which colorectal tumor cells may lose surface expression of HLA class I molecules. Several independent mechanisms have been identified, including loss or mutations in beta 2-microglobulin genes, loss of HLA heavy chain genes, selective lack of expression of HLA alleles, and regulatory defects in HLA expression including loss of expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…(18,26,27) We and other investigators have demonstrated loss of HLA haplotype secondary to loss of heterozygosity mainly in cell lines and tissue sections from solid tumors. (22,(28)(29)(30)(31)(32)(33)(34)(35) We know of no report concerning HLA haplotype deletion in leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(18,26,27) We and other investigators have demonstrated loss of HLA haplotype secondary to loss of heterozygosity mainly in cell lines and tissue sections from solid tumors. (22,(28)(29)(30)(31)(32)(33)(34)(35) We know of no report concerning HLA haplotype deletion in leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Loss or down-regulation of HLA class I antigen expression has been demonstrated in a variety of tumors, and can have several causes: absence of β2M or transporter associated with antigen processing (TAP) expression; (17)(18)(19)(20) loss of heterozygosity, large deletions, or mitotic recombination in chromosome 6; (18,21,22) transcriptional down-regulation; (23)(24)(25) and point mutation, partial deletion, or somatic recombination. (18,26,27) We and other investigators have demonstrated loss of HLA haplotype secondary to loss of heterozygosity mainly in cell lines and tissue sections from solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation silences MLH1 expression and is frequently found with increasing age and in the proximal colon (Issa, 2000;Momparler and Bovenzi, 2000). A number of mechanisms other than ␤2m-expression defects are known that can account for down-regulation of HLA-I expression, such as genetic defects in the coding sequences of the HLA-I heavy chains (Jimenez et al, 1999;Koopman et al, 2000), regulatory defects (Browning et al, 1996), or defects in antigen processing and presentation, eg, in transporter associated with antigen processing. For instance, the latter were shown to account for a large proportion of HLA-I alterations in breast cancer (Kaklamanis et al, 1995), head and neck squamous cell carcinomas (Feenstra et al, 1999;Seliger et al, 1997), and 14% of colorectal carcinomas (Kaklamanis et al, 1994).…”
Section: Hla-i and Prognosis In Colorectal Cancermentioning
confidence: 99%
“…Development of the cytotoxic immune response depends on the expression of MHC class I molecules. These are shown to be down-regulated in human cancers [124] and in response to aberrant Wnt signalling [96], and may contribute to a tumour's ability to escape the host defences.…”
Section: The Wnt Signalling Pathway In Cancermentioning
confidence: 99%